Does economic growth benefit the poor? Evidence from the 2015-2018 growth episode - Celia M. Reyes; Arkin A. Arboneda; Ronina D. Asis; Anna Rita P. Vargas (Philippine Institute for Development Studies (PIDS), 2020)
The Philippines is generally winning its fight against poverty as the magnitude and incidence of poverty, income gap, and severity of poverty have all decreased in 2018. Poverty decomposition analysis shows that both economic growth and income redistribution factors have equally contributed to the declining poverty levels. However, the decline in poverty gap and poverty severity is largely explained by income redistribution. On the other hand, while inequality measures indicate a more equal distribution of income, poverty indicators continue to vary widely across the regions. Given these developments, the Philippine government has been enacting different policies and programs, including the conditional cash transfer program, social pension program, progressive taxation policies, and universal access to tertiary education policy, to further address poverty and inequality in country in pursuit of eradicating all forms of poverty as targeted by the Sustainable Development Goals.
Keywords: 330; Philippines; poverty; poverty decomposition; inequality